Associations of Cigarette Smoking and Polymorphisms in Brain-Derived Neurotrophic Factor and Catechol-O-Methyltransferase with Neurocognition in Alcohol Dependent Individuals during Early Abstinence - Durazzo, Timothy; Hutchison, Kent; Fryer, Susanna; Mon, Anderson; Meyerhoff, Dieter (Frontiers in Pharmacology, 2012)
Chronic cigarette smoking and polymorphisms in brain-derived neurotrophic factor (BDNF) and catechol-o-methyltransferase (COMT) are associated with neurocognition in normal controls and those with various neuropsychiatric conditions. The influence of these polymorphisms on neurocognition in alcohol dependence is unclear. The goal of this report was to investigate the associations of single nucleotide polymorphisms (SNP) in BDNF Val66Met and COMT Val158Met with neurocognition in a treatment-seeking alcohol dependent cohort and determine if neurocognitive differences between non-smokers and smokers previously observed in this cohort persist when controlled for these functional SNPs. Genotyping was conducted on 70 primarily male treatment-seeking alcohol dependent participants (ALC) who completed a comprehensive neuropsychological battery after 33 ± 9 days of monitored abstinence. Smoking ALC performed significantly worse than non-smoking ALC on the domains of auditory-verbal and visuospatial learning and memory, cognitive efficiency, general intelligence, processing speed and global neurocognition. In smoking ALC, greater number of years of smoking over lifetime was related to poorer performance on multiple domains. COMT Met homozygotes were superior to Val homozygotes on measures of executive skills and showed trends for higher general intelligence and visuospatial skills, while COMT Val/Met heterozygotes showed significantly better general intelligence than Val homozygotes. COMT Val homozygotes performed better than heterozygotes on auditory-verbal memory. BDNF genotype was not related to any neurocognitive domain. The findings are consistent with studies in normal controls and neuropsychiatric cohorts that observed COMT Met carriers showed better performance on measures of executive skills and general intelligence. Overall, the findings support to the expanding clinical movement to make smoking cessation programs available at the inception of treatment.